Bryocorinae Baerensprung, 1860 (Hemiptera: Heteroptera: Miridae) of European Russia and the Caucasus: synopsis and key to species - Konstantinov, Fedor V.; Neimorovets, Vladimir V. (Zootaxa, 2021)
This paper provides a review of the plant bug subfamily Bryocorinae (Hemiptera: Miridae) of European Russia and the Caucasus. Although several bryocorine species are widely used as biological control agents, species delimitation remains challenging even in the relatively well-studied European fauna. We provide diagnoses, distribution data, host information, and illustrated keys to six genera and 21 species found in the region. The following new records are given: Dicyphus (B.) albonasutus Wagner, 1951 (Crimea and Caucasus, North Ossetia), Dicyphus (B.) digitalidis Josifov, 1958 (Caucasus, Abkhazia), Dicyphus (B.) geniculatus (Fieber, 1858) (Armenia and Ingushetia), Dicyphus (D.) epilobii Reuter 1883 (Abkhazia and Ingushetia), Dicyphus (D.) hyalinipennis Burmeister, 1835 (Armenia). Previous records of Dicyphus (B.) annulatus (Wolff, 1804) from the Northern Caucasus (Konstantinov & Zinovyeva 2017), and Crimea were based on misidentifications and should be referred to D. albonasutus. Records of Dicyphus (D.) pallidus (Herrich-Schaeffer, 1836) from Krasnodar Terr and Azerbaijan should be referred to D. errans (Wolff, 1804).